 # Solve 2 3 4 6

## Solve 2 3 4 6

### Solve 2/3 + 4/6?

Solve 2/3 + 4/6?

4/6 can be simplified to 2/3.

So now we have:

2/3 + 2/3

Since the two have the same difference, we can add numbers.

2/3 + 2/3 = 4/3

Therefore, 2/3 + 4/6 = 4/3

You can subtract the first 4/6 by the factor of 2 ... 4/2 = 2 and 6/2 = 3. So change 4/6 to 2/3.

Now 2/3 + 2/3. Just add a counter (first digit).

You get 4/3, which is 1/3.

## Solve 2 3 4 6

When it comes to equality, the word solution is used.

In that case, the word assessment would be appropriate.

2/3 + 4/6 = 4/6 + 4/6 = 8/6 = 4/3 = 1ÂÂ… "

Collect the common component by multiplying by 2 before and below. Then add it directly by adding the element and retaining the general part. Then

4/6 +4/6 = 8/6 = 4/3

## Solve 2 3 4 6

To find 2/3 + 4/6, you must first find a common denominator, that is, find the first common number before tables 3 and 6 = 6.

1x3 = 3 1x6 = 6

2x3 = 6 2x6 = 12

Coming soon

2/3 + 4/6 = 2 * 2/6 + 4/6 = 4/6 +4/6 = 8/6 = 4/3.

For 2/3, to make 6 worth, you have to multiply 3 by 2 and 2 by 2 ...

4/3

When adding different things, they must have the same difference. You can multiply 4/6 by 1/2 to get 2/3, since now the tricks are the same, you can add them ... The answer is 4/3.

All you need is one letter (the number below the line). In this case, it's 6. So you need to multiply the numbers 2 and 3 by the appropriate part of 2/3 space. Note: The letter was not added

## Solve 2 3 4 6

Now 2/3 is 4/6, so if you add it up, you get 8/6, which is reduced to 1 2/6, which in turn is reduced to 1/3.

1 1/3.

## Solve 2 3 4 6 Solve 2/3 + 4/6?

4/6 can be simplified to 2/3.

So now we have:

2/3 + 2/3.

Since they both have the same dominator, we can add numbers.

2/3 + 2/3 = 4/3.

Therefore, 2/3 + 4/6 = 4/3.

You 4 ...

Now 2/3 + 2/3. Only add one counter (first digit).

You get 4/3, which is 1 1/3.